The Study About Influence Of Contextual Learning Models Type Modelling On The Learning Outcom Christian Religion Education Of The Subjects Of Class VII Students At Smpn 2 Palangka Raya - Juan Pratama Nyalat; Yuel; Joni Saputra (Institut Agama Kristen Negeri Manado, 2024)
The problem in this research is that the learning outcomes of students in Christian Religious Education subjects at SMP Negeri 2 Palangka Raya class VII are below the Minimum Completeness Criteria (KKM). This can occur due to the use of less effective learning models. Therefore, researchers conducted research to test the effect of using a contextual learning model of the modeling type in comparing the influence between contextual learning models of the modeling type and conventional learning models. The method in this research is a quantitative method with an experimental research type. Meanwhile, the research data analysis technique used in this research is Mann Whitney. The research results shown by the Mann Whitney test obtained sig results. 0.000 < 0.05, and there is a difference in the increase in the average value of 3% which is higher for the experimental class compared to the control class. So it can be concluded that the contextual learning model of the modeling type has a better influence than the conventional learning model on learning outcomes in Christian Religious Education subjects for class VII students at SMP Negeri 2 Palangka Raya.